2008
DOI: 10.1016/j.clinph.2008.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory postural adjustments associated with a forward leg raising in children: Effects of age, segmental acceleration and sensory context

Abstract: a b s t r a c tObjective: The purpose of this study was to determine the influence of age, segmental acceleration and sensory context on anticipatory postural adjustments (APAs) in a forward leg raising task. Methods: Three groups of 11 children, aged 8, 10 and 12, and 12 adults, aged 20 to 26, were instructed to perform this movement at maximal (MAXIMAL) and sub-maximal segmental accelerations and in normal (CONTROL), no vision (NV) and perturbed proprioception conditions (VIB). The generation and calibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Contrary with the study of Teasdale and Simoneau (2001) in which participants had to respond as fast as possible to an unpredictable auditory stimulus and were simultaneously asked to sway as little as possible, our participants were not asked to focus on their stance when vibrations were applied at both agonists and antagonists muscles of the ankles. Bilateral double vibrations of muscles anterior and posterior to the ankle muscles may have produced uncertainty about the location of the body in space (Horak et al 1990;Palluel et al 2008a;Peterka 2002). This may have affected the ability to bind vision and touch as visuo-tactile integration strongly relies on the representation of a common spatial source.…”
Section: Discussionmentioning
confidence: 96%
“…Contrary with the study of Teasdale and Simoneau (2001) in which participants had to respond as fast as possible to an unpredictable auditory stimulus and were simultaneously asked to sway as little as possible, our participants were not asked to focus on their stance when vibrations were applied at both agonists and antagonists muscles of the ankles. Bilateral double vibrations of muscles anterior and posterior to the ankle muscles may have produced uncertainty about the location of the body in space (Horak et al 1990;Palluel et al 2008a;Peterka 2002). This may have affected the ability to bind vision and touch as visuo-tactile integration strongly relies on the representation of a common spatial source.…”
Section: Discussionmentioning
confidence: 96%
“…Experience and learning are believed to be essential in the development of APAs (Kazennikov et al 2008;. In addition, it is likely that proprioceptive information, which is used to build up internal representations of the effects of voluntary movements on posture and equilibrium (Massion 1998;, is essential for the development of APAs (Palluel et al 2008). However, it has been reported that proprioceptive information processing is altered in individuals with CP (Riquelme and Montoya 2010).…”
Section: Discussionmentioning
confidence: 97%
“…APAs are affected by the inclination of the floor [7], the magnitude of the forthcoming movement [8], posture [9], age [10,11], and several neurodegenerative diseases, such as Parkinson's disease [12], Huntington's chorea [13], and Down's syndrome. APAs are also affected in stroke patients and amputees [5].…”
Section: Introductionmentioning
confidence: 99%